"Ethics in Business and Value Addition" A Case: Polyhydron Pvt. Ltd, Belgaum-Karnataka (India) - Kumar, D. N. S.; Khera, Spardha (Prabandhan: Indian Journal of Management, 2008)
This paper throws light on the importance of ethics in business and the value addition because of ethical conduct, and exemplifies the same with a case study on Polyhydron Pvt. Ltd., Belgaum.Polyhydron Pvt. Ltd., is a flag ship company of Polyhydron group of companies. It was established in 1982 and manufactures Hydraulic Radial Piston Pumps, Valves and Accessories. Its products are priced unbeatably low, and Polyhydron Pvt. Ltd. has changed the price marginally in the last 25 years. Polyhydron is known for its 'Ethical Management'. At Polyhydron Pvt. Ltd., honesty is not a policy, but 'the policy'. It believes in building quality from the SOURCE. Self-inspection is the Best Inspection is also its policy.In conclusion, in the new millennium it has become imperative for businesses throughout the world to conduct business ethically to survive, develop, and flourish. The process of globalization of the Indian economy will make it inevitable for all the Indian business to evolve into ethical organizations; else their very survival will be at stake in the seamless global economy of the new millennium.